Teaching reading by using visual scaffolding strategy for the eighth grade students of SMPN 1 Takeran - Fahrul Aditiansyah (Universitas PGRI Madiun, 2017)
The purpose of this study was to describe the application of the Visual Scaffolding strategy in reading in the eighth grade at SMPN 1 Takeran. Visual scaffolding is a strategy that is given to students for reading learning. In reading learning, students feel reading is one of the skills that is difficult to master where students have difficulty interpreting, and explain the meaning of meaning in the text. For that teachers use the Visual Scaffolding strategy where in teaching and learning activities teachers use visual media such as images, videos and movements to make students better understand teaching materials.